AN INVESTİGATİON OF THE RELATİONSHİP BETWEEN SOCİAL MEDİA ADDİCTİON WİTH ALTRUİSM AND EGOCENTRİSM (Third Sector Social Economic Review, 2021)
This study with a simple random sampling design aimed to determine the relationship between social media addiction and altruism and egocentrism in adolescents and explain factors predicting social media addiction. The sample of the study consisted of 898 adolescents in the 14-18 age group, a little more than half of whom (51.7%) were female students (n=464). According to the findings, the majority (92%) of the participants was using “WhatsApp.” There was a significant difference between sex and the use of “Facebook” (X2=137.220; df=1; p
Keywords: social media addiction; adolescent; altruism; egocentrism; social media